An eight-coordinate zinc complex containing the highly pre-organized ligand 1,10-phenanthroline-2,9-dicarboxylic acid: solvothermal synthesis, supramolecular structure and CSD studies - Mirzaei, Masoud; Hassanpoor, Azam; Alizadeh, Hanie; Gohari, Mahnaz; Blake, Alexander J. (Elsevier, 2018)
A new anionic coordination complex of Zn(II) containing the highly pre-organized ligand 1,10-phenanthroline-2,9-dicarboxylate (PDA), (H3O)2[Zn(PDA)2]·2CH3NO2·2H2O·(1), has been synthesized by solvothermal methods and characterized by elemental analysis, infrared spectroscopy and single-crystal X-ray diffraction. The last of these techniques revealed a coordination sphere around Zn(II) consisting of four N atoms and four O donors from two 1,10-phenanthroline-2,9-dicarboxylate ligands which features a distorted dodecahedral geometry. The ionic coordination motifs in 1 are held together by intermolecular O―H…O, N―H…O and C―H…O hydrogen bonding, C―H... π and π−π stacking interactions, to produce an extended 2D architecture.